Enhanced Anticancer Effects of Intratumorally Injected Electrostatic Doxorubicin-Loaded Click-Type Crosslinked Hyaluronic Acid Hydrogel - Ju, Hyeon Jin; Kim, Min Ju; Kim, Shina; Son, Kyung Eun; Lee, Min Young; Kim, Han Su; Kim, Moon Suk (Advanced Therapeutics, 2024)
Injectable depots have received increasing notoriety as local drug delivery vehicles for tumor treatment. Here, an intratumoral formulation of doxorubicin (Dox) is proposed that relies on the electrostatic interaction between the carboxylic group of click-type crosslinked hyaluronic acid (Cx-HA) and cationic Dox to achieve effective tumor treatment. The Dox-loaded click-type crosslinked HA (Cx-HA-Dox) formulation exhibits adequate injectability for intratumoral injection and rapidly forms a depot at the tumor site, remaining inside the tumor for over 18 days. This enhances the bioavailability and therapeutic efficacy of Dox primarily within the tumor, minimizing off-target side effects. Intratumoral injection of Cx-HA-Dox in animal models significantly suppresses tumor growth, as evidenced by a decrease in tumor volume over time. Histological analysis reveals limited angiogenesis in the treated tumors and an increase in the number of large apoptotic cells. Overall, the findings suggest that the electrostatically crosslinked Cx-HA-Dox depot can synergistically enhance the anticancer activity of Dox.
Keywords: click-type crosslinking; electrostatic interaction; intratumoral injection; tumor suppression